Determination of the sound power of a machine inside an industrial room by the inversion method - PIECHOWICZ, Janusz (Archives of Acoustics, 2009)
Utilisation of the substitute sources system consisting of monopole sound sources is one of the methods of sound sources modelling in the industry. The knowledge of the actual acoustic pressure distribution around industrial sound sources is necessary for determination of the parameters of such models. In order to satisfy requirements, the distribution of acoustic pressure amplitudes as well as the distribution of phase shift angles between acoustic signals are to be determined. The presented investigations constitute a part of the research program related to the application of inversion methods in the assessment of acoustic parameters of machines operating under industrial conditions, as well as to the comparative analysis of the hereby obtained results with the results obtainable by other methods of testing.